2015
DOI: 10.1016/j.immuni.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Macrophage Colony-Stimulating Factor-Activated Eosinophils Promote Interleukin-23 Driven Chronic Colitis

Abstract: SummaryThe role of intestinal eosinophils in immune homeostasis is enigmatic and the molecular signals that drive them from protective to tissue damaging are unknown. Most commonly associated with Th2 cell-mediated diseases, we describe a role for eosinophils as crucial effectors of the interleukin-23 (IL-23)-granulocyte macrophage colony-stimulating factor (GM-CSF) axis in colitis. Chronic intestinal inflammation was characterized by increased bone marrow eosinopoiesis and accumulation of activated intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(168 citation statements)
references
References 53 publications
7
161
0
Order By: Relevance
“…5, E and F) and that baseline inflammatory mechanisms (Fig. 5G) were not affected, along with previous studies demonstrating the role for eosinophils and their granule proteins in the disease outcomes (13,16), supports our notion that eosinophil cytolysis is the main mechanistic link between cyclophilin D deficiency and improved disease outcomes. Future studies using cell-specific deficiency will further clarify this point.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5, E and F) and that baseline inflammatory mechanisms (Fig. 5G) were not affected, along with previous studies demonstrating the role for eosinophils and their granule proteins in the disease outcomes (13,16), supports our notion that eosinophil cytolysis is the main mechanistic link between cyclophilin D deficiency and improved disease outcomes. Future studies using cell-specific deficiency will further clarify this point.…”
Section: Discussionsupporting
confidence: 90%
“…When treated with apoptosis inducers, Ppif Ϫ/Ϫ eosinophils showed no significant difference in apoptosis or necrosis from wild-type (WT) eosinophils. Since we and others previously showed that eosinophils and eosinophil granule proteins have an important role in colitis (13,16), we tested the role of cyclophilin D in a dextran sodium sulfate (DSS)-induced colitis model. Although the baseline inflammatory parameters were comparable between WT and PPIF deficiency, Ppif Ϫ/Ϫ mice exhibited decreased clinical outcomes, as evidenced by weight loss, colon length, and histological changes, which correlated with significantly reduced eosinophil cytolysis in the colon.…”
mentioning
confidence: 99%
“…As with IL-13, it is secreted mainly by ILC2, but functions predominantly as an eosinophil recruitment and growth factor. [79][80][81] Eosinophils, which make up only a fraction of circulating leukocytes, are relatively abundant in the intestinal tract 82 and have traditionally been associated with combating parasites. There are little data, however, to suggest that deficiency in either IL-5 or eosinophils affects the polarization of protective immunity or by extension the outcome of infection, despite that eosinophil-derived mediators can skew dendritic cells to promote type 2 immunity.…”
Section: Transmissionmentioning
confidence: 99%
“…More importantly, independent studies revealed that GMCSF is required for classical EAE development in mice, especially by activating microglia or mobilizing inflammatory myeloid lineages to the inflammation site [109,110]. Studies from Fiona Powrie's lab more recently showed that IL-23-dependent production of GMCSF also contributes to the pathogenesis of colitis in naïve CD4 + T-cell transfer-and Hepaticus-induced models of murine IBD [111,112]. In both models, GMCSF was shown to promote eosinophil recruitment and activation in the colon which was needed for pathogenesis.…”
Section: Gmcsfmentioning
confidence: 99%